A Study On Mental Status And Academic Performance Of The Students After Pandemic Period - Arthiga Devi, S. (International Journal of Advanced Research in Peace, Harmony and Education, 2023)
This study is aimed to understand and assess the relationship of Mental status and Academic Performance of school students. The result showed that the Mental status and Academic Performance are positively correlated with the total sample and the Sub samples (Gender, Locale and type of management). Mental Status of the students highly depends on their Academic Performance.